2019
DOI: 10.1371/journal.pone.0201081
|View full text |Cite
|
Sign up to set email alerts
|

Is Osmia bicornis an adequate regulatory surrogate? Comparing its acute contact sensitivity to Apis mellifera

Abstract: Bees provide essential ecosystem services and help maintain floral biodiversity. However, there is an ongoing decline of wild and domesticated bee species. Since agricultural pesticide use is a key driver of this process, there is a need for a protective risk assessment. To achieve a more protective registration process, two bee species, Osmia bicornis / Osmia cornuta and Bombus terrestris , were proposed by the European Food Safety Authority… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
(52 reference statements)
3
19
1
Order By: Relevance
“…Though risk assessments of PPPs on honeybees have been extrapolated to non-Apis bees (EFSA 2013), several studies have reported interspecific differences between Apis and non-Apis bee species in responses to various stressors including exposure to agrochemicals (Scott-Dupree et al 2009;Thompson 2016;Rundlöf et al 2015;Uhl et al 2019;Heard et al 2017;Arena and Sgolastra 2014). It may not always be reasonable to extrapolate from honeybees to evaluate the risk on other bee species, due to the differences in the exposure profiles for each species (Thompson and Hunt 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Though risk assessments of PPPs on honeybees have been extrapolated to non-Apis bees (EFSA 2013), several studies have reported interspecific differences between Apis and non-Apis bee species in responses to various stressors including exposure to agrochemicals (Scott-Dupree et al 2009;Thompson 2016;Rundlöf et al 2015;Uhl et al 2019;Heard et al 2017;Arena and Sgolastra 2014). It may not always be reasonable to extrapolate from honeybees to evaluate the risk on other bee species, due to the differences in the exposure profiles for each species (Thompson and Hunt 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In combination with the extensive experience and resulting robust test methodology makes A. mellifera solid choice as screening level test species. In contrast the relative sensitivity data indicates that the two recently developed model species Bombus terrestris and Osmia bicornis for the European risk assessment process are comparatively resilient to a range of insecticides, which in turn means that including them in the screening step will likely not make the risk assessment more protective for bees from a sensitivity perspective [12,13,66,67].…”
Section: Risk Assessment Considerationsmentioning
confidence: 96%
“…Based on our literature search, there are no investigations of the effects of chronic contact exposure on lethality. Dimethoate, an organophosphate pesticide commonly used as a reference toxicant, has been evaluated in contact and oral toxicity tests as a technical grade active ingredient and in formulated products using Osmia spp., M. rotundata and N. melanderi [37][38][39][40][41][42][43]. However, the available dataset is too fragmented to thoroughly evaluate for reproducibility and cross-species sensitivity.…”
Section: Review Of 23 Publications Identified 185 Investigations Of the Lethal Effects Of Pesticides On Adult (179 Investigations) And Immentioning
confidence: 99%
“…For that reason, species that incorporate leaf parts into their nests (i.e., M. rotundata) or excavate belowground nests (i.e., N. melanderi, E. pruinosa) may be vulnerable to additional pesticide exposure routes resulting in cumulative exposure to larger quantities of pesticide over time [1]. Coupling the potential for increased exposure levels with evidence for differential sensitivity to pesticides [22,38,107] leads us to recommend completion of studies conducted in parallel to clarify the meaningful differences between species and, thus, inform the future need for conducting these laboratory tests.…”
Section: Risk Assessment Considerationsmentioning
confidence: 99%